Periareolar augmentation mastopexy: A new approach dealing with the cases as tuberous breasts - Roberto Moltó-García; María Eloísa Villaverde-Doménech; Virina González-Alonso; Francisco Ripoll-Orts; Eduardo Simon-Sanz (Indian Journal of Plastic Surgery)
Background: Periareolar augmentation mastopexy is one of the most demanded operations at Plastic Surgery clinics. Nevertheless, it is one of the leads of malpractice claims in United States caused by the high patient expectations and the standard surgical techniques which may result in common complications. The aim of this report is to present a new surgical approach to solve these complications. Methods: After establishing a working hypothesis, we performed a revision study of our patients and we came to the following conclusion: in order to perform a periareolar mastopexy for ptosis correction, breast has to be tuberous at any level and to have abnormally short inferior pole. These findings may explain the main complications from periareolar augmentation mastopexy with the standard surgical techniques. Consequently, we started a prospective observational study including 56 patients following a new surgical technique which deals the cases as tuberous breasts. Results: During three years, fifty-six periareolar mastopexies were performed with this new surgical approach with one year follow-up. No major complications were observed and 40 of the patients (71%) described the results as very positive. Conclusion: “If a periareolar mastopexy can be performed, then it must be a tuberous breast”. According to this, a new surgical technique for periareolar augmentation mastopexy has been developed obtaining an improvement in our surgical results and achieving a totally different view on this pathology, which has not been reported in literature yet.